PERANCANGAN ALAT BANTU ANGKAT HASIL PANEN BUAH NAGA YANG ERGONOMIS DI PERKEBUNAN DRAGON FRUIT FARM - Rifaldi, Rifaldi Hakiki; Zet, Sri (LPPM Universitas Putera Batam, 2026)
Manual transportation of harvested crops using conventional wheelbarrows poses a high ergonomic risk to workers due to non-ergonomic working postures. Awkward postures such as bending, shoulder elevation, and excessive load on the back and arms may lead to musculoskeletal disorders and reduced comfort and productivity. This study aims to analyze working posture risks during the crop transportation process, design an ergonomic trolley based on workers’ anthropometric data, and evaluate changes in risk levels before and after the trolley implementation. The research methods include Rapid Entire Body Assessment (REBA) to assess working postures, anthropometric measurements to determine trolley dimensions, and Ergonomic Function Deployment (EFD) to translate user requirements into design specifications. The results indicate that the initial working condition using a conventional wheelbarrow produced a REBA score of 12, classified as a very high ergonomic risk. After the implementation of the ergonomic trolley, the REBA score decreased to 1, indicating a very low risk level. In addition, the load capacity increased from 40–50 kg to 60–70 kg per transport cycle, thereby improving work efficiency. The study concludes that the ergonomic trolley effectively improves working posture, reduces ergonomic risk, and enhances comfort, safety, and work effectiveness.